2018
DOI: 10.1161/jaha.117.007863
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pressor Response to Psychosocial Stress Is Dependent on Endothelium‐Derived Endothelin‐1

Abstract: BackgroundAcute psychosocial stress provokes increases in circulating endothelin‐1 (ET‐1) levels in humans and animal models. However, key questions about the physiological function and cellular source of stress‐induced ET‐1 remain unanswered. We hypothesized that endothelium‐derived ET‐1 contributes to the acute pressor response to stress via activation of the endothelin A receptor.Methods and ResultsAdult male vascular endothelium‐specific ET‐1 knockout mice and control mice that were homozygous for the flox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 67 publications
(161 reference statements)
0
11
0
Order By: Relevance
“…ET‐1 is released in response to a number of stimuli including acute and chronic stress, 38 hyperosmolality, 39 high sodium intake 39 and hypoxia 40 . Obesity is a disease of chronic tissue hypoxia, 41 a known stimulus for ET‐1 production from endothelial cells through activation of hypoxia inducible factor alpha (HIF‐1α) 42 .…”
Section: Et‐1 In Obesity: Clinical Implicationsmentioning
confidence: 99%
“…ET‐1 is released in response to a number of stimuli including acute and chronic stress, 38 hyperosmolality, 39 high sodium intake 39 and hypoxia 40 . Obesity is a disease of chronic tissue hypoxia, 41 a known stimulus for ET‐1 production from endothelial cells through activation of hypoxia inducible factor alpha (HIF‐1α) 42 .…”
Section: Et‐1 In Obesity: Clinical Implicationsmentioning
confidence: 99%
“…Stress, whether acute or chronic, increases ET-1 production. For instance, air-jet stress and psychosocial stress in response to cage switching in rodents cause an acute increase in plasma ET-1 [17,18]. ET-1 is also thought to play a role in early life stressinduced changes in cardiovascular function in rodents [19].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, both experimental and population-based studies demonstrated increased ET-1 levels following psychosocial stress exposure in healthy and diseased subjects (21,56,59,83,140). Endothelin-1 is a potent vasoconstrictor and an important mediator of CVD development following chronic upregulation of the acute stress response (214).…”
Section: Hpa Axis Hormones and Endothelial Dysfunctionmentioning
confidence: 99%
“…Endothelin-1 is a potent vasoconstrictor and an important mediator of CVD development following chronic upregulation of the acute stress response (214). Moreover, a study conducted in 2018 found that ET-1 contributes to the hypertensive response following acute stress exposure by binding to the endothelin-A receptor (59).…”
Section: Hpa Axis Hormones and Endothelial Dysfunctionmentioning
confidence: 99%